Proposals for Financial Education activities based on Critical Mathematics Education - Argena, Suellen Roberta de Jesus; Munhoz, Regina Helena (Educação Matemática Debate, 2024)
Financial Education can be understood as a set of concepts and has been included in school curricula. Reflecting on its importance and looking for ways to approach it in the school environment, a pedagogical notebook was produced. The aim of this paper is therefore to present the evaluation of this material, carried out by teachers who analyzed the activities and learning environments proposed. It was noted that they have the potential to become scenarios for research involving Financial Education with a theoretical basis in Educação Matemática Crítica (Critical Mathematics Education — EMC). The research is characterized as qualitative and the content analysis described by Gomes (2016) was used to interpret the data. The results show that, although challenging, it is possible to develop teaching materials based on EMC.